Interactions of hydrocolloids and sonicated-gluten proteins - Ribotta, Pablo Daniel (2005)
The aims of this article were to explore the nature of the interactions between certain commercial hydrocolloids and sonicated-gluten proteins and to evaluate their relation to bread quality. Dough rheology and bread quality were affected in different ways by the addition of hydrocolloids. Pectin and l-carrageenan strengthened wheat dough and sodium alginate augmented the extensibility of dough. In addition, sodium alginate and pectin improve loaf volume and all the hydrocolloids tested decreased the initial bread crumb firmness and chewiness. This work demonstrated that carrageenan isoforms and pectin (sulphated and carboxylated hydrocolloids, respectively) can form hydrophilic complexes with gluten proteins and the capacity of complexation appears to be related to the density of the anionic group in the hydrocolloidl-carrageenan strengthened wheat dough and sodium alginate augmented the extensibility of dough. In addition, sodium alginate and pectin improve loaf volume and all the hydrocolloids tested decreased the initial bread crumb firmness and chewiness. This work demonstrated that carrageenan isoforms and pectin (sulphated and carboxylated hydrocolloids, respectively) can form hydrophilic complexes with gluten proteins and the capacity of complexation appears to be related to the density of the anionic group in the hydrocolloid.